PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA DALAM MENUNJANG PEMBIAYAAN PEMBANGUNAN DI DESA BITUNURIS KECAMATAN SALIBABU KABUPATEN KEPULAUAN TALAUD - BAWIAS, RIZAL; Pangkey, Masje Silija; Rorong, Arie Junus (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT: The success of the village government can run smoothly and well being supported by manyfactors one village the financial factor because it is impossible for the village to be able to carry out thevillage administration effectively and efficiently without adequate financial support. This is due to thefinancial capacity of the village depends on the size and variety of sources of income as financial resourcesare owned by the village. Therefore, the leadership of the village head and village, excavation andmanagement of financial resources through the village of APBDes should be pursued in order to financewith establishment of the village and reached the village government administration efficient and effectiveas well as holding on to the Regulation of the Minister of Home Affairs Number 37 Year 2007, on GeneralGuidelines for Financial Management of the Village. The aim of this study is to describe, analyze anddetermine how the government's role in the management of village Budget Financing village inSupporting Rural Development in the District Bitunuris Salibabu Talaud Islands.This study used qualitative data analysis method presented in descriptive with purposivesampling technique of sampling / sample aiming the number of informants there are fifteen informants.Of existing research, the role of government in the village of budget revenue and expendituremanagement in support of rural development funding has not been completely worked well because thereis no budget is unclear or incomplete data, the condition of the village and village regulation system onlyfamilial but with flaws there are all the village officials work well together to seek the implementation ofAPBDes / village with a transparent financial accountability and participatory.Keywords:Management, Budget and buying rural (APBDes), Development.